(untitled) (Research, Society and Development, 2021)
So far, evidence suggests that the risk of the newborn (NB) being infected during hospitalization for childbirth is low, but only when the necessary care is taken to protect these patients from the mother’s infectious respiratory secretions and when they are performed prevention measures in the bedroom and breastfeeding. The work aims to expose through the analysis of scientific articles the main aspects involved in SARS-CoV-2 infection in newborn patients. This is a literature review of a qualitative and systematic nature carried out between the years 2019 to 2021. There is a concern raised about the risk that COVID-19 infection can represent for the fetus. Whether vertical propagation of the virus is possible and what consequences it would have is not entirely clear, but the risk appears relatively small. Although it is not possible to assume the repercussion for neonatal patients, it is possible to avoid mortality by adopting established protocols. It is essential to constantly seek to clarify the mechanisms and forms of transmission in these patients, in view of this, the realization of new, more complete scientific studies that address this issue is necessary.